Assistance in Preparing Quality Documents for Private Universities in Kampar Regency: Pendampingan Penyusunan Dokumen Mutu Bagi Perguruan Tinggi Swasta di Kabupaten Kampar - Zulkarnain, Zulkarnain; Suryanita, Reni; Zul, Delita; Olivia, Yessi (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2024)
Quality assurance of higher education is carried out through the determination, implementation, evaluation, control, and improvement of Higher Education Standards (SPT) known as the PPEPP cycle. Each university is expected to be able to develop an SPMI pattern that is appropriate for the conditions of the university itself. However, not all universities have the same understanding of the implementation of SPMI. For this reason, this community service activity aims to help two universities in Kampar Regency, Riau Province, namely: Universitas Pahlawan Tuanku Tambusai and STIE Bangkinang. Although these two universities already have an Internal Quality Assurance Institution, the adequacy of SPMI documents has not been fully met according to standards. The community service activity began by distributing an initial survey on participants' understanding of SPMI at their respective universities. Furthermore, the community service activity was filled with the provision of materials and a final survey to analyze changes in the level of participants' understanding of the material given to participants. The survey results showed that there had been an increase in participants' understanding in compiling and archiving SPMI documents.